Sibling relationships and visual impairment: investigating their bond with a focus on the role of social play - Battistin, Tiziana; Zanatta, Alessia; Zanardo, Vincenzo; Brugnaro, Luca; Mercuriali, Elena; Reffo, Maria Eleonora (Frontiers in Psychology, 2025)
Social play has a key role in the development of social skills in child development, especially in early and middle childhood through peer interaction. Siblings serve very often as children’s first peers, shaping each other’s overall development throughout life. This mixed study investigates the quality of sibling relationships by giving voice to siblings with and without visual impairment, with a focus on the role of social play in their daily lives. Our findings confirm a harmonious relationship quality and the importance of social play in the sibling bond, suggesting that social play may serve as a protective factor for their mental health.